Development of a Serious Game as an Educational Tool for Obesity Prevention - Kusumah, Akmal Fauzi; Kurniawan, Rahadian (Department of Informatics Universitas Islam Indonesia, 2024)
As technology develops, many things can be used as methods in obesity prevention education, one of which is by creating an obesity prevention educational game. This educational game is designed with the aim of raising public awareness of what causes obesity in a different way. Through the development of the Digital Game Based Learning-Instructional Design (DGBL-ID) model, this research includes needs analysis, design, development, quality assurance, and game implementation & evaluation. Needs analysis involved an online survey of people with obesity, showing their interest in games as an educational medium. Game design involved storyboards and flowcharts, with the story being about Bono looking for healthy food for his obese friend. Development is done using Unity with an interface that includes the main menu, level list, stage list, game play, and game results. Quality assurance will involve black box testing and implementation evaluation by respondents. This article produces an obesity prevention educational game that is expected to increase public awareness about the risks of obesity through an interactive and informative game experience.